4x-2(x+4)
4x-2x+8
(4x-2x)+8
2x+8
2(x+4)
c=2x+8
2007-01-02 15:25:15
·
answer #1
·
answered by daddyspanksalot 5
·
0⤊
3⤋
>>> 4x – 2(x + 4)
First: distribute the 2 with both terms in the parenthesis >
4x – 2(x) - 2(4)
4x – 2x - 8
Sec: combine "like" terms >
2x - 8
2007-01-02 15:27:17
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
Simplifying
4x + -2(x + 4)
Reorder the terms:
4x + -2(4 + x)
4x + (4 * -2 + x * -2)
4x + (-8 + -2x)
Reorder the terms:
-8 + 4x + -2x
Combine like terms: 4x + -2x = 2x
-8 + 2x
2007-01-03 02:41:29
·
answer #3
·
answered by SHIBZ 2
·
1⤊
0⤋
The answer is A.
4x-2(x+4)
4x-2x+8
2x+8
2007-01-02 15:29:10
·
answer #4
·
answered by Kikyo 5
·
1⤊
0⤋
4x – 2(x + 4) =
4x - 2x -8 =
2x -8
2x = 8
x = 8:2
x = 4
Solution: {x E R | x = 4}
Answer is in alternative a.
<>
2007-01-02 15:39:08
·
answer #5
·
answered by aeiou 7
·
1⤊
0⤋
4x-2(x+4)
first use the distributive property. you get:
4x-2x-8
then add like terms(4x and -2x). you get:
2x-8, so your answer would be a.
hope that helps!
2007-01-02 15:27:56
·
answer #6
·
answered by Ashley 2
·
1⤊
0⤋
4x - 2(x + 4) => 4x -2x -8 =. 2x -8 => 2(x-4). ans = a.
2007-01-02 15:25:12
·
answer #7
·
answered by flyfisher_20750 3
·
1⤊
0⤋
4x – 2(x + 4)=4x-2x-8=2x-8
a.2x – 8
is correct
2007-01-02 15:25:24
·
answer #8
·
answered by yupchagee 7
·
2⤊
0⤋
4x - 2(x + 4) =
4x - 2x - 8 =
2x - 8
The correct answer is a.
2007-01-03 07:21:28
·
answer #9
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
Don't forget to distribute!
4x - 2x - 2(4)
4x - 2x - 8
2x - 8
A
2007-01-02 15:25:45
·
answer #10
·
answered by teekshi33 4
·
2⤊
0⤋
a.2x-8
2007-01-02 15:22:44
·
answer #11
·
answered by raj 7
·
2⤊
0⤋